Development of Puzzle Media Based on Culturally Responsive Learning to Improve Students' Reading Skills - Rika Juwita Hasibuan; Safran Safran (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study aims to develop puzzle-based learning media based on Culturally Responsive Teaching (CRT) to improve the reading skills of first-grade students at SD Negeri 100309 Sibio-bio. This study uses the Research and Development (R&D) method with the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 18 first-grade elementary school students. Data collection techniques included tests, questionnaires, interviews, and documentation, while data analysis used quantitative and qualitative descriptive techniques based on percentages. The results of the study show that the CRT-based puzzle media developed meet the criteria of being valid, practical, and effective. Validation results showed scores of 77.3% from media experts, 80% from material experts, and 80% from language experts, categorized as valid. From the aspect of practicality, the teacher's response scored 86.2% and the students' response 86.5%, both of which fall into the very practical category. In addition, the effectiveness test results showed a significant improvement in students' reading skills, with the average pre-test score of 49.6 (low category) increasing to 91.1 (high category) in the post-test. An N-Gain score of 0.8 indicates a high improvement category.